Hawks Engineering Works: At the Crossroads of Growth. Issue 2 (September 2019) - Shahid, Muhammad Shehryar; Ahsan, Saad Raafay
This case revolves around Hawks Engineering Works (HEW), an automotive parts supplier based in Lahore, Pakistan. Registered as a private partnership between the founding partners, Shahid and Akram, in 1987. HEW specializes in the supply of door hinges and door lock strikers for different automobiles. HEW has monopolized the production of these specialized parts and counts the 'big three' OEMs, i.e., Honda, Toyota and Suzuki, amongst its customers. While HEW has been an exemplary company over the years, winning many 'best vendor' awards for quality and delivery, recently, the company has been plagued with complaints from their biggest customers. These complaints center on miscommunication from HEW's side on different matters, as well as late deliveries and falling quality standards. HEW's management must thus evaluate what has gone wrong while the company has grown from a small entrepreneurial concern to a mid-sized organization. For this purpose, students must first understand the founders' entrepreneurial journey. This will lead them to analyze HEW's growth trajectory over the years, to identify its current positioning on this growth spectrum, and seek out and attempt to correct any misalignments in the company's key management factors, which will help determine its future growth prospects.